Future alternatives for educational leadership diversity, inclusion, equity and democracy - Netolicky, Deborah M. (Routledge, Taylor & Francis Group, 2022)
This book offers provocations for what's now and what's next in educational leadership, simultaneously bringing the field both back to its basics--of equity, democracy, humanity, and education for all--and forward to productive, innovative, and necessary possibilities. Written during the pandemic reality of 2020, this collection shares the global voices and expertise of prominent and emerging leaders, scholars, and practitioners in education from the UK, the United States, South America, Canada, Europe, Australia, and the Middle East. The authors engage with the complexities and uncertainties of leading in education. They examine research, reflections, and real stories from which school leaders, education system leaders, policymakers, and researchers in the field of educational leadership, can learn, and in which they will find honesty, authority, and inspiration to guide the future of the field. The new perspectives and hopeful alternatives presented in this outstanding book are essential to researchers, school leaders, and policymakers, and are key to advancing education into positive and democratic futures.